Developing Interactive Multimedia Through Ispring on Indonesian Language Learning with The Insights of Islamic Values in Madrasah Ibtidaiyah - Muchamad Fauyan (Al Ibtida: Jurnal Pendidikan Guru MI, 2019)
AbstractThis research was motivated by the Indonesian learning which contains very little of moral and character messages and the lack of learning resources, resulting in less interesting and unpleasant learning which lead the development of four aspects of language skills as learning objectives to be unachieved. Therefore, this research aimed to find out (1) the eligibility of interactive multimedia on Indonesian learning with Islamic insight based on the assessment of media experts and material experts, and (2) the quality of interactive multimedia on Indonesian learning with Islamic insight based on the assessment of students and teachers. This research and development are using ADDIE model. The procedures of this research include the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were fourth grade students of Madrasah Ibtidaiyah (MI) Pringlangu 02 Pekalongan City. The results of this study are: (1) interactive multimedia products for Indonesian learning with Islamic insight was assessed by material experts with a score of 21.5 in the very eligible category and assessed by media experts with a score of 49.5 in the eligible category; (2) the quality of interactive multimedia for Indonesian learning with Islamic insight is very good based on the assessment of students and teachers. Thus, the use of multimedia for Indonesian learning is needed because it is a source of learning that can improve learning performance, as well as seeding the value of Islamic characters in students.Keywords: interactive multimedia, indonesian learning, Islamic values.AbstrakPenelitian ini dilatarbelakangi oleh pembelajaran bahasa Indonesia yang kering dari pesan-pesan moral dan karakter serta minimnya sumber belajar yang mengakibatkan pembelajarannya kurang menarik dan tidak menyenangkan yang pada gilirannya pengembangan empat aspek keterampilan berbahasa sebagai tujuan pembelajaran tidak tercapai. Oleh karena itu, penelitian ini bertujuan untuk menghasilkan (1) kelayakan multimedia interaktif pada pembelajaran bahasa Indonesia berwawasan nilai-nilai Islami berdasarkan penilaian ahli guru dan siswa, dan (2) kualitas multimedia interaktif pada pembelajaran bahasa Indonesia berwawasan nilai-nilai Islami berdasarkan penilaian siswa dan guru. Penelitian pengembangan ini (Research and Development) menggunakan model ADDIE. Prosedur penelitian ini meliputi: tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian ini adalah siswa kelas IV Madrasah Ibtidaiyah (MI) Pringlangu 02 Kota Pekalongan. Hasil penelitian ini adalah: (1) produk multimedia interaktif untuk pembelajaran bahasa Indonesia berwawasan nilai-nilai Islami dinilai oleh ahli materi dengan skor 21,5 berada pada kategori sangat layak dan dinilai oleh ahli media dengan skor 49,5 berada pada kategori layak; (2) kualitas multimedia interaktif untuk pembelajaran bahasa Indonesia berwawasan nilai-nilai Islami adalah sangat baik berdasarkan penilaian siswa dan guru. Dengan demikian, penggunaan multimedia pada pembelajaran bahasa Indonesia diperlukan karena menjadi sumber belajar yang mampu meningkatkan kinerja pembelajaran, sekaligus penyemai nilai-nilai karakter Islami pada siswa.Kata kunci: multimedia interaktif, pembelajaran bahasa Indonesia, nlai-nilai Islam.